Dynamic evolution model of freeway traffic accident risk based on complex network - TANG Zhihui; HUANG Jingru; ZHANG Nan (Shenzhen Daxue xuebao. Ligong ban)
To effectively excavate the patterns in freeway traffic accidents, we propose a method for constructing a freeway traffic accident cause network based on complex network theory. We define the risk propagation mechanism from two aspects: risk structure and risk patterns, and integrate the freeway traffic accident cause network with these mechanisms to establish an evolution model for freeway traffic accident risk. Using data from 201 investigation reports of major highway traffic accidents as examples, risk analysis is conducted. The results show that the risk evolution model based on complex networks is applicable for analyzing freeway traffic accident risks. The model allows the analysis and classification of risk propagation characteristics of each causation factor, enabling the formulation of targeted control strategies. This paper provides a new approach for studying the evolution of freeway traffic accident risk.